A Comparison Study on Co- and Counterrotating Dual-Rotor System with Squeeze Film Dampers and Intermediate Bearing - Fei Wang; Gui-Huo Luo; Shu Yan; Hai-Tao Cui (Shock and Vibration)
Nonlinear dynamic model of a coaxial rotor system was established with a method combining the finite element method and the fixed interface modal synthesis method. Then an implicit time domain method was presented to solve the nonlinear equations of motion; thus dynamic characteristics of the rotor system can be obtained. With nonlinear forces of squeeze film damper and intermediate bearing considered, nonlinear dynamic response characteristics of the co- and counterrotating coaxial rotor system under multiple unbalance forces were studied and compared in this work. It was found that the critical speeds of the corotating system were equal to or slightly higher than those of the counterrotating case due to the gyroscopic moments. The results showed that the unbalance excitation frequencies are dominant in the responses of the rotor system. Besides, due to coupling effect of the intermediate bearing some combinations of the unbalance excitation frequencies were also observed in the spectrogram but the combinations were different for co- and counterrotating cases. Stability and periodicity of the rotor system were investigated with bifurcation diagram, Poincare map, and phase diagram. It was found that the rotor system executes four-period quasi-periodic motion around critical speeds.